Gadjah Mada International Journal Of Business: SQ and the Mediating Effect of Corporate Image on the Relationship between Customer Satisfaction and Customer Loyalty in the Malaysian Hotel Industry - Boon-Liat Cheng (MM UGM, 2013)
Service quality is vital to the success of any service organization. The rapid growth of the Malaysian hotel industry in the 2000’s forced hotel operators to seriously recognize the importance of service improvement in order to gain competitive advantage. This study aims to examine the impact of service quality on customer satisfaction, and how customer satisfaction subsequently affects customer loyalty in the hotel industry in Malaysia. This study also investigates the mediating effect of corporate image on the relationship between customer satisfaction and customer loyalty.